2011
DOI: 10.1038/nn.2746
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin as a direct detector of Ca2+ signals

Abstract: Many forms of signal transduction occur when Ca2+ enters the cytoplasm of a cell. It has been generally thought that there is a fast buffer that rapidly reduces the free Ca2+ level and that it is this buffered level of Ca2+ that triggers downstream biochemical processes, notably the activation of calmodulin (CaM) and the resulting activation of CaM-dependent enzymes. Given the importance of these transduction processes, it is critical to understand exactly how Ca2+ triggers CaM. We have determined the rate at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(212 citation statements)
references
References 30 publications
6
201
0
Order By: Relevance
“…For LTP, we consider that the STDP window is defined by an exponential curve that dictates the instantaneous amount of Ca 2ϩ /calmodulin that will be formed at the time of the postsynaptic spike. In a recent work by Faas et al (2011), the authors have shown that the binding of calmodulin with calcium takes place over a very short timescale, in accordance with our phenomenological description of this process as an instantaneous rise of the corresponding variable at the time of postsynaptic spikes. This variable will be labeled ␦w LTP .…”
Section: Biophysical Correlates Of the Mstdp Modelsupporting
confidence: 80%
“…For LTP, we consider that the STDP window is defined by an exponential curve that dictates the instantaneous amount of Ca 2ϩ /calmodulin that will be formed at the time of the postsynaptic spike. In a recent work by Faas et al (2011), the authors have shown that the binding of calmodulin with calcium takes place over a very short timescale, in accordance with our phenomenological description of this process as an instantaneous rise of the corresponding variable at the time of postsynaptic spikes. This variable will be labeled ␦w LTP .…”
Section: Biophysical Correlates Of the Mstdp Modelsupporting
confidence: 80%
“…Following Ca 2+ entry in response to a graded guidance cue, the pathway begins with the rapid binding of Ca 2+ to CaM to form a Ca 2+ / CaM complex [75]. This activates CaN, PKA, and CaMKII at differing levels on each side of the growth cone, depending on the intracellular Ca 2+ concentration.…”
Section: Downstream Effects Of Calciummentioning
confidence: 99%
“…With regard to biochemical signaling cascades, tiny ∼fA Ca 2+ fluxes, generally believed not to partake in local signaling, could produce ∼μM Ca 2+ signals sufficient to signal locally to molecules like CaM or CaMKII (34). Nanodomain boosting may similarly play a role in the contraction of ventricular myocytes, where controversy exists regarding whether activation of ryanodine receptors can be triggered by the opening of a single Ca V channel [high-fidelity scenario supported by early experimental work (35)(36)(37)(38)], or if the simultaneous opening of ∼10 channels is necessary [as suggested by recent models that take account of the small ∼fA flux through a single Ca V channel at the +50 mV ventricular plateau potential (39)(40)(41)].…”
Section: Significancementioning
confidence: 99%